False-Negative Results in Routine Combined First-Trimester Screening for Down Syndrome in Finland - Marttala, Jaana; Kaijomaa, Marja; Ranta, Jenni; Dahlbacka, Anna; Nieminen, Pentti; Tekay, Aydin; Kokkonen, Hannaleena; Laitinen, Paivi; Ignatius, Jaakko; Romppanen, Jarkko; Heinonen, Seppo; Jarvela, Ilkka; Heikkila, Matti; Yla-Outinen, Ari; Ulander, Veli-Matti; Hamalainen, Esa; Ryynanen, Markku (American Journal of Perinatology, 2012)
We analyzed the frequency and possible causes of false-negative (Fn) screening results in first-trimester combined Down syndrome screening in Finland. During the study period (May 1, 2002, to December 31, 2008), 76,949 voluntary women with singleton pregnancies participated in screening. Maternal age at screening, week of gestation, levels of pregnancy-associated plasma protein-A (PAPP-A), free β-human chorionic gonadotropin (fβ-hCG), and nuchal translucency (NT) measurement were compared and statistically analyzed between true-positive (Tp) and Fn cases. There were a total of 188 Down syndrome cases (1:409) in the screened population; 154 confirmed Tp and 34 Fn cases. Most Fn cases (n = 25) occurred at 12 + 0 to 13 + 6 weeks' gestation and only nine Fn cases presented between 10 and 11 weeks' gestation. According to the logistic regression analysis, the NT measurement was the most powerful discriminating factor in Fn screening results and accounted for 37.2% of Fn results. The second most important factor was fβ-hCG, adding 14.0% to R2, followed by PAPP-A, which contributed a further 14.3%. The chosen parameters explain 83.9% of Fn results, but 16.1% remain due to unknown factor(s). All investigated parameters contributed to Fn screening results, but fetal NT was the most discriminating factor leading to an Fn screening result.
Keywords: Down syndrome; combined screening; true positive; false negative